Higher Education in Malaysia: Access, Equity and Quality - Mukherjee, Hena; Jabir S, Singh; Fernandez-Chung, Rozilini M.; Marimuthu, T (ISEAS–Yusof Ishak Institute, 2017)
Since independence in 1957, Malaysia has transformed itself from an agrarian to an increasingly industrial and globalized economy. Malaysia was formed in 1963 comprising Malaya, Sabah, Sarawak and Singapore, with the last leaving the group in 1965. In the country of 30-odd million, 62.1 per cent are Malays and other indigenous groups, 21.8 per cent Chinese, 6.5 per cent Indians and 9.6 per cent Others (includes 8.7 per cent non-citizens). Malaya and Singapore were served by the University of Malaya (UM), located in Singapore, until 1957 when a branch campus was established in Kuala Lumpur. In 1962, it split into two entities, University of Malaya and University of Singapore, as befits the two sovereign states.